On the role of magnetic field intensity for better micro-structural characterization during Barkhausen Noise analysis - Yusufzai, M.Z.K.; Vashista, M. (Institute of Physics Publishing, 2018)
Barkhausen Noise analysis is a popular and preferred technique for micro-structural characterization. The root mean square value and peak value of Barkhausen Noise burst are important parameters to assess the micro-hardness and residual stress. Barkhausen Noise burst can be enveloped using a curve known as Barkhausen Noise profile. Peak position of profile changes with change in micro-structure. In the present work, raw signal of Barkhausen Noise burst was obtained from Ni based sample at various magnetic field intensity to observe the effect of variation in field intensity on Barkhausen Noise burst. Raw signal was opened using MATLAB to further process for microstructure analysis. Barkhausen Noise analysis parameters such as magnetizing frequency, number of burst, high pass and low pass filter frequency were kept constant and magnetizing field was varied in wide range between 200 Oe to 1200 Oe. The processed profiles of Barkhausen Noise burst obtained at various magnetizing field intensity clearly reveals requirement of optimum magnetic field strength for better characterization of micro-structure. © Published under licence by IOP Publishing Ltd.
Keywords: Barkhausen Noise; Signal Processing; Magnetizing field strength